Bridging the gap evaluation of the effect of Pfizer VISMIN hypertension team perception on performance management practices for their retention - Caulin, Ray
The study shows the components of Pfizer Work Performance namely, OJI, Sales Target, leadership, Supervision, MD calls, MD Reach,Selling skills, Customer Focus, Teamwork,MPOA implementation and Sales Achievement. these parameters were thoroughly discussed along with the PMS ratings of the VISMIN HPN PHRs from 2012 to 2013. Consequently, the study was also able to find out that the respondents have improved their overall PMS rating as indicated by a fewer the number of PHRs who were rated as DNME in 2013 versus 2012. Furthermore, the team has able to manage the expectations on the company by maximizing each component to the best of their ability considering the limited resources, stricter policies and highly genericized market condition. To have fairness among the team respondents, the study also identified that as per management practice on performance, PMS is designed in a two-way system in terms of computing the results of each team member. One of which is system generated (quantitative) by which all the scores are generated by the computer. This includes Sales Achievement,OJI, MD calls and MD reach. On the other hand, the non-system generated (qualitative) are performed through assessment of written Critical Incidents submitted by PHRs. This non-system parameters include Selling Skills, Customer Focus, Teamwork and MPOA implementation. The final PMS result is a combination of the two system. Among the performance drivers, chosen, the study finds out that PHTs' Districts Managers has the highest influence in performance as confirmed by ANOVA. On the other hand, other drivers of performance (aside from Performance Management Practices chosen) among the respondents are also gathered to know their personal aspirations that influence their effort to perform. Based on the interventions of the existing performance management practices by the company, it can be observed that performance management practices of the organization have no significant difference as to drivers of performance and to PMS. Thus, the study results further verify that indicated performance drivers directly affects the retention rate of the VISMIN Hypertension team. Likewise, management initiatives and imperatives to improve performance triggered PHRs to perform and to be retained.